Abstract ID: 175 A EBT3 film calibration approach for the validation of a Monte Carlo internal dosimetry framework. (October 2017) - Frezza, Andrea; Espagnet, Romain; Desport, Corentin; Maneval, Daniel; Després, Philippe
Abstract : Context and objectives: Recent studies have shown the potential benefits of using 177Lu-based Peptide Receptor Radionuclide Therapy (PRRT) in neuroendocrine tumors. For 177Lu-based and other radionuclide therapies, it appears that a robust Monte Carlo-based internal dosimetry framework is highly desirable. Gafchromic EBT3 films can potentially contribute to the validation of such a dosimetry framework, but require an appropriate calibration procedure to account for their energy dependence. Monte Carlo simulations were used to investigate this dependence with 177Lu, and to develop a film calibration procedure with an orthovoltage beam having a quality (Q) and a similar energy dependence. Methods: The physical quantity evaluated in this work was the film equivalent absorbed dose to water f(Q). This was obtained with Geant4 simulations as the ratio of the absorbed dose in water to the absorbed dose in the film displacing a water volume. f(Q) was calculated with different orthovoltage beams and with a 177Lu source placed in a water filled Jaszczak phantom. X-ray beam qualities ranging from 2.24 to 3.22 mm Cu (HVL) were tested, corresponding to peak voltages of [220–300] kVp and effective energies of [115–142] keV. The simulation input spectra were obtained with the SpeckCalc software. 177Lu disintegrations were simulated with Geant4 RadioactiveDecay5.1.1 data. Results: A minimal difference of 0.4% in f(Q) was obtained between 177Lu and an orthovoltage beam quality of 3.07 mm Cu (HVL) having an effective energy of 138 keV (300 kVp). For beams with effective energies ranging from 136 to 142 keV, this difference was <1%. Discussion and conclusion: The optimal orthovoltage beam quality for the calibration of EBT3 film to use with 177Lu was found. The f(Q) does not show a strong kVp dependence in the range explored, and calibration can be performed with a beam having an effective energy of approximately 140 keV and a quality of 3 mm Cu (HVL). This represents the first step towards the validation of a fast GPU-based, in-house Monte Carlo code dedicated to accurate internal dosimetry in nuclear medicine.